Coordinating Ombudsmen and the Judiciary? - Milan Remač (Central European Public Administration Review)
An ombudsman institution is one of the most rapidly developing institutions in modern democratic states. Ombudsmen can be characterised as individual and impartial investigators of administration and its conduct. They act as dispute resolution mechanisms between the state and individuals and sometimes also as solvers of problems of individuals. In order to assess the quality of administrative conduct they use normative standards against which they assess this conduct. However, all these matters are primarily in the hands of the judiciary. The judiciary, notably administrative courts are the most important dispute resolution mechanisms in modern states that assess the administrative conduct against certain normative standards. Thus ombudsmen and the judiciary can be often seen as institutions having relatively similar competences in a relatively similar area, despite retaining numerous differences. They both are approached by the individuals and they can express their opinions about administrative justice. This paper highlights the main findings and recommendations of a comparative legal research carried out in the area of mutual interrelations of ombudsmen and the judiciary. On the examples of three different legal systems (the Netherlands, England and the European Union) the research discusses the possibility of coordination of relations between the ombudsman and the judiciary in connection with the position of these institutions, with their jurisprudence and ombudsprudence and with normative standards they use in their work.